Study of disaster preparedness in Singapore libraries/information centres - Loh, Kim Chuan. (2010)
To librarians and archivists, disasters are unexpected events that cause destruction to their premises or collections or seriously disrupt their daily operations. Disaster planning is an essential component of the overall management plan for libraries. A disaster plan systematically lays down well-thought-out priorities and techniques to meet an emergency so as to minimise loss, bring order out of chaos and restore normal operations as soon as possible.